The Effect of Arm Muscle Strength Training and Eye-Hand Coordination on Top Service Results in Volleyball Junior Athletes (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the effect of arm muscle strength training and eye-hand coordination on improving overhand serve results in junior volleyball athletes. The novelty of this research lies in the combination of two specific types of exercises (push-ups and catching ball throws) that are adapted to the characteristics of early adolescence, as well as their programmed application to groups of junior female athletes. This study used an experimental method with a one-group pretest-posttest design conducted at the Kanaya Volleyball Club, Jambi City. The sample consisted of 12 female athletes aged 12-15 years who were selected through a quota sampling technique. Data collection was carried out using push-up tests, ball catching throws, and overhand serve tests (AAHPER). The results of the paired sample t-test showed a significant increase after being given treatment, with a significance value of 0.000 (p < 0.05). This shows that arm muscle strength training and eye-hand coordination have a positive effect on the overhand serve results of junior athletes.